1998
DOI: 10.1037/0882-7974.13.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Activities and well-being in older age: Effects of self-concept and educational attainment.

Abstract: The positive effect of activities on well-being is proposed to be mediated by self-conceptualizations and facilitated by socioeconomic status. The hypothesized processes were estimated with LISREL VIII using data from a large cross-sectional survey with a sample of 679 adults aged 65 and older who were representative of older adults living in the Detroit area. Findings indicate that the frequency of performing both leisure and productive activities yields an effect on physical health and depression and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 21 publications
10
135
1
5
Order By: Relevance
“…20 These effects are both similar and contrasting to cross-sectional effects reported in Herzog et al (1998). Job satisfaction -understood as the most intrinsic non-economic job reward -positively affects psychological well-being.…”
Section: %mentioning
confidence: 51%
See 2 more Smart Citations
“…20 These effects are both similar and contrasting to cross-sectional effects reported in Herzog et al (1998). Job satisfaction -understood as the most intrinsic non-economic job reward -positively affects psychological well-being.…”
Section: %mentioning
confidence: 51%
“…22 Previous studies also suggest that overall wellbeing is likely to be impaired for those forced into retirement (Bender and Jivan, 2005;Herzog et al, 1998;Gallo et al, 2000;and Kim and Moen, 2002). People are forced into retirement mainly due to health reasons and job displacement (Prudential, 2005).…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…However, results of the Berlin Aging Study indicate that the effect diminishes after adjustment for important confounders (Maier and Klumb 2005). In terms of other health measures, Herzog et al (1998) observed that frequency of productive and leisure activities improves physical health and reduces the risk of depression in older people. Using the American Changing Lives data base associations of volunteering with lower mortality (Musick et al 1999) and with higher self-perceived health and life satisfaction (van Willigen 2000) were found.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing age, however, people define themselves more and more in terms of health and physical functioning, life experiences, and hobbies (Dittmann- Kohli, 1991;Freund & Smith, 1999). Another aspect of this adaptation to aging seems to be that activity and agency become important parts of the selfdefinition in old age, as they are no longer self-evident (Freund & Smith, 1999;Herzog, Franks, Markus, & Holmberg, 1998).…”
Section: Evidence On the Development Of The Life Pragmatics Of Personmentioning
confidence: 99%